New Understanding Biology for Advanced Level Fourth Edition - Toole, Glenn; Toole, Susan ([S.l.] : Oxford University Press, 2014)
This is a fully accessible text that is comprehensive, without excessive detail which can cause confusion. It is separated into divisions into manageable sections, with summary tables of information to help organise study and revision. It supports practicals, coursework and all the core content of the course. It includes notebook sections, explaining other topics which you need to know about for Biology, such as pH and mole calculations. Project suggestions are provided for coursework, with lots of up-to-date examination questions for practice.